Lack of Anonymity and Secondary Traumatic Stress in Rural Nurses - Marilyn A. Swan; Barbara B. Hobbs (Rural Nurse Organization; Binghamton University, 2021)
Purpose: The purpose was to determine the prevalence of lack of anonymity (LA) and secondary traumatic stress (STS) among nurses; determine if nurses' LA and STS differ by population density and examine the relationship between lack of anonymity and STS. Design and Method: A descriptive correlational study examined LA and STS in a random sample of 271 nurses from counties with differing population densities (rural, micropolitan and metropolitan) of a Midwestern US State. A 3-group design was used to examine the relationship between LA and STS in nurses, living and working in these counties. Data on lack of anonymity, secondary trauma and demographics were collected through online questionnaires. Findings: Rural nurses had a higher prevalence of LA than micropolitan and metropolitan nurses. While the prevalence of STS among rural nurses was higher than either micropolitan or metropolitan nurses; there was no difference in STS among the three population groups. Lack of anonymity and STS were related; however, analysis revealed that LA and STS are inversely correlated, indicating that as LA increases, STS decreases. A majority of rural nurses (90%) reported living in a rural community prior to their 18th birthday. Conclusions: Rural nurses experience STS at similar rates as their metropolitan and micropolitan counterparts, indicating that population density may not be a factor related to the development of STS. LA appears to have a positive effect on reducing STS in rural nurses. Clinical Relevance: The study advanced the understanding of LA and STS among nurses who live and work in different population densities. The social support within rural health care facilities and communities may play a role in mitigating the effects of indirect stress. Keywords: rural, rural nursing, lack of anonymity, traumatic stress DOI: https://doi.org/10.14574/ojrnhc.v21i1.651